In vitro antibacterial properties of AT-2266, a new pyridonecarboxylic acid. - Nakamura, S (1983)
AT-2266, 1-ethyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)-1,8-naphthyridine-3 -carboxylic acid, is a new pyridonecarboxylic acid derivative with broad and potent antibacterial activity. It inhibited some gram-positive bacteria, such as staphylococci and Bacillus subtilis, and most gram-negative bacteria, including Serratia marcescens, Pseudomonas aeruginosa, Haemophilus influenzae, and Campylobacter jejuni, at concentrations of 0.1 to 0.78 microgram/ml, and most gram-positive bacteria, glucose-nonfermenters, and Mycoplasma pneumoniae at concentrations of 1.56 to 12.5 micrograms/ml. Most of the clinical isolates tested were as susceptible to AT-2266 as were laboratory strains. The antibacterial potency of AT-2266 was higher than those of pipemidic acid and nalidixic acid and similar to that of norfloxacin. AT-2266 was not cross-resistant with antibiotics and inhibited most highly nalidixic acid-resistant bacteria at concentrations of 1.56 to 3.13 micrograms/ml. Its activity was barely affected by the addition of horse serum or sodium cholate but weakened by lowering the medium pH or increasing the inoculum size. AT-2266 was bactericidal at concentrations near its minimal inhibitory concentrations. Frequencies of mutants resistant to 10 micrograms of AT-2266 per ml were lower than 4.0 x 10(-9).